Prediction of kick direction from kinematics during the soccer penalty kick - Li, Y.; Alexander, M. J. L.; Glazebrook, C. M.; Leiter, J. (International Journal of Kinesiology & Sports Science, 2015)
Background: Speed and direction of the ball are key factors in successful soccer penalty kicks. The kinematics that contribute to the kick direction are unclear. Purpose: The purpose of the study was (1) to compare the differences in instep kick kinematics between left and right kick directions; (2) to determine the significant factors that predict kick direction. Method: Four digital video cameras (80 Hz) collected data from eleven experienced female soccer players during instep penalty kicks to the left and right. Video analysis software (Dartfish Team Pro 6.0) was used to process and analyze the video files. Results: Paired t-tests indicated that several variables before ball contact were different. The linear regression included three variables (support foot orientation, support foot position behind the ball and approach angle) to best predict kick directions (R2 = 75.6%, p < .01). Conclusion: The results may be useful for goalkeepers to anticipate kick direction before ball contact to gain a better chance to save the penalty kick.